The motivation of activity of civil servants as a means to improve the efficiency of the public civil service - Kh. M. Bekmurzieva (Управление)
The article has devoted to topical issues of motivation of employees of state bodies in the Russian Federation. The human factor is the main element of labor productivity and increase the efficiency of the organization. The development of a complex for improving the work of civil servants is one of the most important direction in increasing the efficiency of the public civil service. Civil servants -are the foundation of the state apparatus. In modern conditions, the effective functioning of the state apparatus is impossible without the active participation of civil servants in achieving national goals and objectives. The effectiveness of the activities of civil servants depends largely on their interest in the performance of official duties at a high level. One method of increasing the efficiency of the civil service can be a well-designed system of motivation. In order to avoid mismatch in understanding the motivation system, the author has formed the basic conceptual apparatus on the topic. It has established that the main means of managing the motivation of civil servants in Russia at present is cash payments. The author presents the components of the salary of a civil servant. The necessity of reform of public servants has substantiated. According to the results of the study conducted by the author, possible directions for improving the work activities of civil servants have formulated. A set of measures to improve the civil service in the Russian Federation has proposed, primarily, the introduction of an employment contract according to the «effective contract» principle is proposing. It has established that in relation to each public servant, when concluding an effective contract, his labor function, indicators and criteria for evaluating the effectiveness of activities should be specified, the amount of remuneration, the amount of incentives for achieving collective results of labor should be established. The main criteria for evaluating the activities of civil servants has proposed.